The influence of upper-body strength on flat-water sprint kayak performance in elite athletes - McKean, M. R.; Burkett, B. J. (International Journal of Sports Physiology and Performance, 2014)
Dry-land strength training is a fundamental component for elite kayak performance. The aims of this research were 3-fold: 1st, to determine the relationship between performance time and strength scores for elite kayakers; 2nd, to identify how strength changes (gains or losses) over 3 training y relate with changes in performance time for elite kayakers; and 3rd, to compare the progression in performance times for elite athletes with the top 3 performers from the national championships. The performance data for 15 elite male and 10 elite female kayakers were collected over 2 y. This group was reduced to 9 men and 8 women in the 3rd and final year. There were direct and significant correlations between strength scores and performance times across the 3 y. Bench-press 1RM increased by 34.8% for men and 42.3% for women. Over the 3 seasons, mean 1000-m time decreased by approximately 4.8%, 500-m times decreased by 7.3% (women), and 200-m times decreased by 9.1%. The women`s 500-m changed from 11.9% difference from medalists to within 1.1% during the 3 y. During the 3 y of this study a change in 1-repetitionmaximum (1RM) bench press of 13% for men and 6.5% in women coincided with a change in performance times of 1%. For 1RM pull-up a change of 10% in men and 2.3% in women coincided with a change in performance times of 1%.